Consumer Perceptions Aeki Cerita Kopi of Coffee Shop against Coffee Culture as a Community Lifestyle in Medan City - Gumay, Vita Sari; Ginting, Carles; Pohan, Syafruddin (Budapest International Research and Critics University, 2021)
The purpose of this research is to find out consumer perceptions Aeki Cerita Kopi of coffee shop against coffee culture as a community lifestyle in Medan City. The method in this study uses a qualitative method with a phenomenological approach. The location of the research that was taken was Aeki Cerita Kopi of coffee shop which was located on Jalan Kirana Raya No. 38, Central Petisah, Medan Petisah District, Medan City. The results showed that consumer perceptions Aeki Cerita Kopi of coffee shop through consumer lifestyles were oriented towards coffee beverage products. Even though consumers at home are already enjoying coffee drinks or the like like in a shop, consumers still buy at the coffee shop. Environmental factors greatly influence consumers to drink coffee in a coffee shop, both in the home environment, in the office environment, and in the campus environment.Â